Galactic synchrotron emission and the far-infrared-radio correlation at high redshift - Schober, Jennifer; Schleicher, Dominik R. G.; Klessen, Ralf S. (The astrophysical journal, 2016)
Theoretical scenarios, including the turbulent small-scale dynamo, predict that strong magnetic fields already exist in young galaxies. Based on the assumption of energy equipartition between magnetic fields and turbulence, we determine the galactic synchrotron flux as a function of redshift z. Galaxies in the early universe are different from local galaxies, in particular, the former have more intense star formation. To cover a large range of conditions, we consider two different systems: one model galaxy comparable to the Milky Way and one typical high-z starburst galaxy. We include a model of the steady-state cosmic ray spectrum and find that synchrotron emission can be detected up to cosmological redshifts with current and future radio telescopes.